Promoting forest conservation through ecotourism income? - Wunder, Sven (Center for International Forestry Research, 1999)
A principal criterion for classifying a tourism operation as 'ecotourism' is that local residents at the site should receive substantial economic benefits, which serve both to raise local living standards and as enhanced incentives for nature conservation. This paper sets out a methodological framework for analysis of the alleged participation-income-conservation link, and applies it to the Cuyabeno Wildlife Reserve in the Ecuadorian Amazon region. Three Cuyabeno ethnic groups involved in tourism, the Quichuas, Siona-Secoyas and Cofans, are characterised by different tourism participation models, ranging from autonomous operations to pure salary employment. Results do not support the frequently held belief that autonomous operations are 'better off' by yielding higher local benefits; rather, income size is determined by the site-specific degree of tourism specialisation, which largely depends on the tourist appeal and level of conservation of the natural site. Annual tourism cash flows are found to be much higher than previously estimated (from US$ 15 000-50 000 per village), which represents a significant rise in local purchasing power. In terms of conservation incentives, this study confirmed that income from tourism tends to change local attitudes and behaviour, such as reducing overexploitation, creating 'untouchable' zones and user quotas. The more autonomous the operation, the more incentive exists to rationalise resource use. Also, the mere fact that labour time is invested in tourism leaves less opportunity for hunting and other activities that may have been practised unsustainably in the past. Further, tourism income helps to protect the Cuyabeno Reserve against important external threats, such as oil drilling and squatter colonisation. Recommendations include proposals for gradually augmenting local participation, strengthening both incentives and tourist operations in the fields of food production, handicrafts and the training of local tourist guides. Even with these safeguards, the nexus of social-economic-environmental change will often come in clusters that make it impossible to distinguish between 'desirable' and 'undesirable' impacts, in the unambiguous manner suggested by the axioms of ecotourism.